Effective Refractive Error Coverage (eREC) among Elementary School Students in Dasan Agung Community Health Center, Mataram (2024) - Aliyyu, Aisah; Nintyastuti, Isna Kusuma; Nasrul, Monalisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Refractive errors such as myopia and astigmatism, if uncorrected, can hinder academic achievement. The Effective Refractive Error Coverage (eREC) indicator was developed to measure the effectiveness of eye health services in addressing refractive errors. However, eREC data in Indonesia is still scarce. actively participated in measuring the value of the Effective Refractive Error Coverage (eREC) indicator in her home area, Mataram City, West Nusa Tenggara. This cross-sectional observational study used cluster random sampling and involved 105 fifth- and sixth-grade students aged 11–13 from three elementary schools within the Dasan Agung Community Health Center (Puskesmas) area of Mataram City. Visual acuity was measured using a logMAR chart, followed by pinhole testing and subjective refraction by an ophthalmologist. The eREC categories included Met Need, Unmet Need, and Undermet Need. The prevalence of refractive errors was 11.67%, consisting of 6.67% myopia and 1.9% astigmatism. No cases of hyperopia were found. The eREC score was 0%, with no students meeting the criteria for Met Need, 5.71% categorized as Unmet Need, and 0.95% as Undermet Need. Most students (77.1%) had never had an eye examination, and 3.85% reported feeling embarrassed about wearing glasses due to social stigma. The eREC score of 0% highlights significant gaps in eye health services in the study area. Key risk factors include lack of prior eye screening, excessive screen time, and close work habits. Interventions such as eye health education, regular screening in schools, and access to affordable corrective lenses are crucial to increasing eye care coverage and helping achieve the global eREC target by 2030.